The relationship between selected kinematic parameters and lengths of jumps on the ski-flying competition - Vodicar, J.; Jost, B. (Kinesiology, 2011)
The objective of this study was to analyse selected kinematic parameters (time of flying, in-run velocity, take-off velocity, out-run velocity, height of flying at 17 m, height of flying at 75 m, height of flying at 120 m, aerodynamic index at 17 m, aerodynamic index at 75 m, aerodynamic index at 120 m) of the best world-class ski jumpers participating in the two final individual competitions (Friday and Sunday) of the Ski-Flying World Cup at Planica, Slovenia in 2009 (HS 215 m). All jumps were recorded with three video cameras operating at 50 fps, following the jumpers at the early flight phase (17 m from the take-off edge) and in the middle phase of flying (75 m and 120 m from the take-off edge). The ski jumpers were divided into three statistically significantly differentiated quality groups according to their jump lengths in all three rounds (Fprob.=.01). By means of correlation analysis and single-factor analysis of variance, a smaller number of statistically significant correlations between the defined kinematic variables and the jump length were determined. The differences in the vertical height of flying confirmed a tendency towards positive correlations between this variable and the jump length (rmin=.42, rmax=.79). The group of the best ski jumpers demonstrated a statistically significant higher vertical height of flying curve in all the three competitive rounds at the points of 75 m (Fprob. were between .00 and .08) and 120 m (Fprob.=.01). The best group of ski jumpers had better aerodynamic positions in the flight phase, especially at the point of 75 m (Sunday, the first round, r =-.73; p =.00) and 120 m (Sunday competition in both rounds, Fprob.=.01).